(untitled) (PERcursos Linguísticos, 2020)
For philosophers and sociologists, the act of taking one’s own life, although apparently individual, is surrounded by social circumstances, since suicide is confined to a population. Compared to heterosexual and cistern groups, the propensity for suicide in the LGBTI community is five times higher. We start, then, from the problem of those who are subject to LGBTI even today with speeches that objectify their bodies and lead some of them to mental illness and suicide attempts. With the dissemination of access and effects of digital media, statements about suicidal and emerging events and accumulate in the virtual environment, which also ensures visibility to the heteronormativity fatalities. This way, thinking with Michel Foucault, intends to analyze three YouTube videos related to suicide attempts, investigating the effects of the truth generated by the parresiastic discursivization of suicide attempts by LGBTI individuals in cyberspace. The methodology used is a descriptive-interpretative approach, of qualitative quality. We mainly mobilize the postulates of Foucaultian Discursive Studies, with an emphasis on the actions of individuals, discourse body, participation and confession. We verified the extent to which resistance causes incisions through almost lethal sacrifices that gain resonance on digital networks.